2016
DOI: 10.1177/2057047315625340
|View full text |Cite
|
Sign up to set email alerts
|

Gauging aging: Expert and public understandings of aging in America

Abstract: Understanding how people make sense of social issues is a fundamental aspect of communications research. In this piece, we apply theory from psychological anthropology to provide a new perspective on this core feature of communication and argue for the importance of considering culture in applied communications research. Drawing on a study of the implicit understandings and patterns of reasoning that Americans use to think about the process of aging and older adults, we show how the theory of cultural models c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(58 citation statements)
references
References 37 publications
0
51
0
Order By: Relevance
“…These findings suggest that preserving the ability to perceive aging also as a time for gains and growth will also serve to promote enhanced well-being for individuals throughout adulthood. Given rampant misconceptions in the popular culture that aging is a time of crisis, loss and decline, many individuals simply do not expect that positive age-related changes may be a possibility (Lindland, Fond, Haydon, & Kendall-Taylor, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that preserving the ability to perceive aging also as a time for gains and growth will also serve to promote enhanced well-being for individuals throughout adulthood. Given rampant misconceptions in the popular culture that aging is a time of crisis, loss and decline, many individuals simply do not expect that positive age-related changes may be a possibility (Lindland, Fond, Haydon, & Kendall-Taylor, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…After reviewing FWI recommendations, we identified that our framing of workforce issues could be improved. 3 We found value in the "building momentum" metaphor that FWI proposed. This metaphor emphasizes that we can "gather momentum through the build-up of experience and insights" over time, which makes a compelling case for the important roles geriatrics healthcare professionals play in keeping health care attuned to concepts like frailty, which will play an increasingly significant role in quality care as more of us age.…”
Section: 3mentioning
confidence: 82%
“…2 Our goal is to reduce our reliance on terms that might impede others from hearing what geriatrics experts have to say because of the language we use. 2,3 We are delighted to report that the Editors-in-Chief of our other AGS journals followed our lead, and we hope other journals will too. [4][5][6] We want to be clear that the AGS and its journals will not stop talking about age-related disability, frailty, functional limitations, multimorbidity, decline, and death.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The core of this cultural model, which has been found to shape public thinking about other social issues in North American culture (Lindland, Kendall-Taylor, Haydon, & Fond, 2016;Kendall-Taylor, McCollum, & Manuel, 2009;Hirschman, 2003;Triandis, 1989), is the assumption that the outcomes that people experience-specifically outcomes related to health and wellbeing-are primarily, if not exclusively, the result of individual choices, drive, and willpower. According to this assumption, contextual factors are largely irrelevant because outcomes are the result of individuals making good choices (or not).…”
Section: Individualismmentioning
confidence: 99%